Zum Gedenken an Magdalene Schoch (1897-1987) - Nicolaysen, Rainer; Krause, Eckart (Hamburger Universitätsreden Neue Folge, 2008)
From the introduction:"In an academic ceremony on June 15, 2006, Lecture Hall J in the main building of the University of Hamburg was named in Magdalene-Schoch-Hörsaal - the fifth name given according to the program launched in 1999 for naming restored lecture halls after scientists from Hamburg who were expelled from the "Third Reich". [...] This issue of Hamburg University Speeches documents the speeches given at the ceremony [....] The subsequent printed original texts by Magdalene Schoch are not legal essays, but two autobiographical writings that were previously difficult or even inaccessible; one authored shortly before the beginning of the "Third Reich", the other, in English, after its end. [...] The collection of texts is supplemented by a documentary explaining the origin of the decision to use Magdalene Schoch's name."